(untitled) (Geography and Tourism, 2018)
The present article shows the importance of landscape studies, and in particular, landscape mapping for education about nature. It also discusses the relevance of developing landscape educational trails in national parks. The functions of educational paths and their educational roles are outlined. The design and characterization of the landscape trail through the National Park “Skole Beskids” in order to show the diversity of the landscapes both in the Park, and in the general area of the Skole Beskids.